Conflict in the Career Decision Schemes of High Aspiration Youth - Cochran, Larry; Giza, Linda (Canadian Journal of Counselling and Psychotherapy, 2011)
This study investigated the degree and scope of conflicts among ten career values. Eighty-four IOth and Ilth graders with high occupational aspirations rated ten individually selected occupations on ten standard career values. It was found that about every third substantial relation among values involved conflict, and that there was at least one conflict for every pair of values